Ant colony system application to macrocell overlap removal. - Alupoaei, S.
We present a novel macrocell overlap removal algorithm, based on the ant colony optimization metaheuristic. The procedure generates a feasible placement from a relative placement with overlaps produced by some placement algorithms such as quadratic programming and force-directed. It uses the concept of ant colonies, a set of agents that work together to improve an existing solution. Each ant in the colony will generate a placement based on the relative positions of the cells and feedback information about the best placements generated by previous colonies. The solution of each ant is improved by using a local optimization procedure which reduces the unused space. The worst runtime is O(n3), but the average runtime can be reduced to O(n2).
Keywords: Ant colony optimization; Ant colony system application; Feasible placement; Feedback information; Macrocell overlap removal algorithm; Placement algorithms; Quadratic programming